A Stochastic Framework for Public Debt Sustainability Analysis - Di Bella, Gabriel (IMF Working Papers; Working Paper ;, 2008)
This paper proposes a framework for public debt sustainability analysis (DSA) that is complementary to that generally used by IFIs. The DSA in this paper has three components: (i) an integrated and consistent accounting framework for the Consolidated Public Sector (CPS); (ii) the estimation of an appropriate, and country-specific debt threshold, following the approach proposed by Reinhart, Rogoff and Savastano (2003); and (iii) a method for the calculation of the CPS primary balance to achieve the desired debt targets, without resorting to ad-hoc assumptions for the values of the macroeconomic variables during the planning horizon, in the spirit of Garcia and Rigobon (2004) and Celasun, Debrun and Ostry (2006). The paper uses this approach to analyze the sustainability of the Dominican Republic's Public Debt.